Oligosaccharides from the seeds of Dolichos lablab L. promote gut microbial metabolite L-arginine production to alleviate cyclophosphamide-induced immunosuppression - Liu, Ben; Jin, Jiayi; Zhou, Yuming; Shang, Zhipeng; Meng, Peng; Du, Maoru; Geng, Feng; Gao, Xue; Zhao, Feng; Su, Zhenguo; Pan, Xiaohong (Frontiers in Immunology, 2025)
IntroductionDolichos lablab L. is a nutritionally and medicinally significant legume, yet research on its bioactive oligosaccharides remains limited. This study investigates the potential of Dolichos lablab L. oligosaccharides to ameliorate cyclophosphamide (CTX)-induced immunosuppression and intestinal damage.MethodsCrude oligosaccharides were purified to yield mixture SRSV (86% sugar content), comprising sucrose, raffinose, stachyose, and verbascose (mass ratio 19:16.8:50:14.2). Immunosuppressed mice (CTX-induced) were treated with SRSV (150 mg/kg). Gut microbiota (GM) diversity was analyzed via 16S rRNA sequencing, and serum metabolites were profiled using metabolomics. GM-depleted mice (antibiotic-treated) and L-arginine supplementation experiments were used for mechanistic validation.ResultsSRSV preserved intestinal villi integrity, reversed CTX-induced immune organ atrophy, and restored the CD4+T/CD8+T ratio. It enhanced bone marrow hematopoiesis, elevated peripheral white blood cell and lymphocyte counts, and modulated serum TNF-α levels. SRSV increased GM diversity, enriching beneficial taxa (e.g., Ruminococcus, UBA1819, Anaerofustis) while reducing pathogenic Atopobiaceae. Antibiotic-induced GM depletion abrogated SRSV’s protective effects. Metabolomics identified L-arginine as a key upregulated metabolite, linked to arginine biosynthesis. L-arginine supplementation alone replicated SRSV’s immunoprotective outcomes.DiscussionSRSV attenuates CTX-induced immunosuppression through GM-dependent mechanisms and L-arginine-mediated immunomodulation. GM integrity is essential for SRSV efficacy, as its depletion abolishes protection. The restitution of L-arginine levels underpins SRSV’s capacity to restore immune homeostasis.ConclusionSRSV from Dolichos lablab L. is a promising natural adjuvant for mitigating chemotherapy-induced immunosuppression and intestinal injury, acting via GM modulation and arginine biosynthesis pathways.